Fluorescent Copper Nanomaterials for Sensing NO2− and Temperature - Wang, Ning; Ga, Lu; Ai, Jun; Wang, Yong (Frontiers in Chemistry, 2022)
In this work, highly fluorescent copper nanomaterials were synthesized by using ascorbic acid as a ligand. The excitation wavelength of copper nanomaterials is 367 nm, and the emission wavelength is 420 nm. The size range is 5–6 nm. Nitrite can selectively quench the fluorescence of copper nanomaterials. Therefore, copper nanomaterials can be used to selectively detect nitrite ions. The linear equation is F = −32.94 c (NO2−) + 8,455, and the correlation coefficient is 0.9435. At the same time, we found that the fluorescence intensity of copper nanomaterials has a good correlation with temperature (20–60°C), which shows that they have great potential in the application of nanothermometers.